Rethinking the scale: inclusive assessment of social-emotional development for autistic preschool children - VonLunen, Mia, author; Daunhauer, Lisa, advisor; Simpson, Erica, committee member (Colorado State University. Libraries, 2025)
Assessment in early childhood ensures children receive adequate challenges and scaffolding to support development. Formative, norm-based assessment measures are used to guide instruction; however, normed assessments are often not reflective of neurodivergent populations. For autistic preschoolers in particular, demonstrating social-emotional growth on a norm-referenced scale is challenging, as students with developmental disorders are underrepresented in the creation of the scale. As such, the present project modifies the Teaching Strategies GOLD, a widely used early childhood assessment tool, to include descriptions of levels and example behaviors that are developmentally appropriate for autistic children ages three to five. Through the inclusion of verbal and non-verbal example behaviors, a wide variety of learners are represented. Additionally, revisions focus on breaking apart levels into smaller progressions. By providing early childhood educators with an inclusive tool of assessment, neurodiverse students have access to accurate progress monitoring.
Keywords: inclusive assessment; autism spectrum disorder (ASD); formative assessment; neurodiversity; early childhood education; preschool